Talking balafons - Zemp, Hugo; Soro, Sikaman (International Library of African Music, 2010)
It is evident that the relationship between natural language and balafon playing goes beyond mere imitation, or rather transposition, of tonemes and long and short syllables. Senufo balafonists not only reproduce linguistic statements: they produce them while also making music. Balafon tunes, with their underlying words, bring into play interactive communication, artistic creativity and aesthetic pleasure. THey bring joy to the musicians and to all those who take part in the event.
Keywords: African Music